2010
DOI: 10.2174/138945010790309939
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of TNF Antagonists Beyond One Year in Adult and Pediatric Inflammatory Bowel Diseases: A Systematic Review

Abstract: The introduction in the mid-1990s of tumor necrosis factor (TNF) antagonists changed the treatment of inflammatory bowel diseases (IBD), Crohn's disease and ulcerative colitis (UC) refractory to conventional medications (corticosteroids, immunomodulators). This review summarizes current data on the long-term efficacy and safety of anti-TNF therapy in IBD beyond 1 year. We searched Medline, the Cochrane Library, Embase, and Ovid Medliner for relevant studies. Infliximab, adalimumab and certolizumab are effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 67 publications
(344 reference statements)
1
21
0
Order By: Relevance
“…After 3 weeks of DSS removal, EVOO diets reduced significantly both COX-2 and iNOS expression versus standard diet, where these proteins were appreciably increased compared to sham group. These results are also consistent with other experimental models where, for example, olive oil inhibited COX-2 immunostaining in IL-10 knockout mice [27], endogenously synthesized n-3 PUFAs downregulated COX-2 expression in DSS-induced colitis in fat-1 mice [31] or n-3 PUFA-rich diet showed beneficial effect via inhibition of COX-2 and iNOS expression, among other inflammatory parameters, in TNBS-induced colitic rats [32].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…After 3 weeks of DSS removal, EVOO diets reduced significantly both COX-2 and iNOS expression versus standard diet, where these proteins were appreciably increased compared to sham group. These results are also consistent with other experimental models where, for example, olive oil inhibited COX-2 immunostaining in IL-10 knockout mice [27], endogenously synthesized n-3 PUFAs downregulated COX-2 expression in DSS-induced colitis in fat-1 mice [31] or n-3 PUFA-rich diet showed beneficial effect via inhibition of COX-2 and iNOS expression, among other inflammatory parameters, in TNBS-induced colitic rats [32].…”
Section: Discussionsupporting
confidence: 90%
“…Cytokines, such as IL-1 and TNF-a, share a multitude of pro-inflammatory properties and are crucial in the amplification of mucosal inflammation in IBD [1,2]. In the last years, TNF-a has been the target of clinical investigations aimed at blocking its activity as a novel form of therapy for UC [27]. Our data showed that in DSS groups fed with EVOO diets, TNF-a values were maintained near to sham controls, which is in line with the aforementioned previous reports, where blocking TNF-a can inhibit the pro-inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of the literature found that colectomy rates in UC patients receiving IFX treatment ranged from 17 to 53% [20]. …”
Section: Discussionmentioning
confidence: 99%
“…It is in these situations especially that biological therapy is applied. It is indicated both for inducing remission during periods of exacerbation of the disease, and for maintaining clinical and endoscopic remission, with or without associated use of other drug classes (14,20,22,24,34,35,(38)(39)(40)43,51) . Initially, severe penetrating perianal disease was the main form of CD with an indication for biological therapy.…”
Section: Biological Therapymentioning
confidence: 99%
“…However, in selected cases of patients with clinical and endoscopic remission for more than two years, the treatment may be discontinued after patient compliance (34) . Monitoring of adverse effects and the possible complications arising from the use of immunosuppressants and biological therapy is extremely important, especially with the aim of avoiding opportunistic infections or even enabling early diagnosis and appropriate treatment.…”
Section: Biological Therapymentioning
confidence: 99%